2017
DOI: 10.1016/j.foodchem.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and volatile profile of chili shrimp paste as affected by irradiation and heat

Abstract: Chili shrimp paste (CSP) is an exotic traditional Southeast Asian condiment prepared using mainly fresh chilies and fermented shrimp paste (belacan) which attributed to strong pungent fishy odor. This study aims to evaluate the effectiveness of electron beam irradiation (EBI) exposure on CSP for microorganisms decontamination, and its physicochemical qualities changes. Changes in capsaicinoid contents and volatile compounds were analyzed using HPLC and GC-MS. Mesophilic bacteria, yeast, mold and pathogenic Ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…It indicated that combination treatment of G+C had a significantly greater antimicrobial activity than C and G. The ability of radiation and cinnamon oil to prevent growth of microorganisms in food has been confirmed by other authors (Cheok et al, 2017;Haute et al, 2016). Huq, Vu, Riedl, Bouchard, and Lacroix (2015) reported that the cinnamon oil significantly improved the radiosensitivity of L. monocytogenes.…”
Section: Microbiological Analysismentioning
confidence: 69%
“…It indicated that combination treatment of G+C had a significantly greater antimicrobial activity than C and G. The ability of radiation and cinnamon oil to prevent growth of microorganisms in food has been confirmed by other authors (Cheok et al, 2017;Haute et al, 2016). Huq, Vu, Riedl, Bouchard, and Lacroix (2015) reported that the cinnamon oil significantly improved the radiosensitivity of L. monocytogenes.…”
Section: Microbiological Analysismentioning
confidence: 69%
“…17 The molecular diversity within capsaicinoids occurs due to the carbon chain, which may present itself as: (i) unsaturated and ramied, as in capsaicin; (ii) saturated and ramied, as in dihydrocapsaicin; or (iii) saturated and linear, as in nonivamide. 59,60 This molecular structure provides the CAPS with an amphiphilic and no basicity behavior, atypically of what is observed in alkaloids in general. 17,59,60 Among the compounds that constitute the capsaicinoids class, only four of them are usually studied due to their higher concentration in situ, 60 these are the major compounds capsaicin and dihydrocapsaicin, and the minor ones homocapsaicin and nordihydrocapsaicin, whose structure can be observed in Fig.…”
Section: Capsaicinoidsmentioning
confidence: 80%
“…Among the substances identied in the volatile prole are thiol methane, dimethyl sulde, dimethyl amine, acetaldehyde, propanal, acetone, 2-nonanone, hexane, acetic acid, 1-pentanol, limonene, pentadecane, ethyl ester propanoic acid, ethanol, 2methyl-1-tetradecene, hexyl n-valerate, b-cubene, b-caryophyllene, butyrate, hexanal, a-pinene, linalool, limonene, hexyl isobutanoate, a-terpineol, methyl salicylate, heptyl isopentanoate, decanoic acid, b-cubebene, germacrene D, 6methyl-4-heptenyl 2-methylpropanoate, pentyl 4-methyl-2pentanoate, ethyl 3-methylpentanoate, 2-butyl acetate, acopaene, byperene, a-humulene, g-cadinene, and acalacorene. 54,60,121,188,189 Pino et al characterized several C. chinense subjects of Habanero and found a specic prole in accordance to fruit colors. 188 Cultivars with red fruits are usually associated with high amounts of hydrocarbons, which are correlated to the biosynthesis of capsaicin and degradation of carotenoids 54,188 while orange-fruits correlate to high quantities of esters.…”
Section: Volatile Compositionmentioning
confidence: 95%
See 1 more Smart Citation
“…The maximum total capsaicinoids (105.9 mg/ 100 g, 103.3 mg/100 g) content including capsaicin, dihydrocapsaicin, and nordihydrocapsaicin were observed in the RPP samples irradiated with a low dose rate of GR (1.8 kGy/h) and EB (1 kGy/s), respectively. Cheok et al (2017) reported that high thermal treatment (80°C, 21.6 min) caused a significant (p \ 0.05) decrease by 62.18, 64.72, and 62.95% in the contents of capsaicin, dihydrocapsaicin, and nordihydrocapsaicin, respectively. Cheon et al 2015reported a significantly (p \ 0.05) increased capsaicinoid levels in RPP after minimal heat treatment at 65°C.…”
Section: Effect Of Irradiation At Different Dose Rates On Capsaicinoimentioning
confidence: 99%